CHALLENGES OF GIRL-CHILD EDUCATION IN A PERIOD OF RECESSIVE ECONOMY IN NIGERIA - Umar, Maimuna Rabo (Sokoto Educational Review, 2018)
Education has been identified as a developmental tool of which no nation could develop without. Sustainable development could only be achieved with the contributions of both sexes, as women play a significant role in the development of any society. The paper traces the geneses of girl child education in an economic recession, so also the relevance of girl child education in economic development such as manpower, skills capacity development. The challenges facing girl child education which include illiteracy, extreme poverty and socio-cultural factors. The paper suggested, among others, that government should not only make girl child education free but also compulsory at all levels to prevent drop out as a result of lack of funding.